GAMBARAN PEMAHAMAN MAHASISWA TERHADAP KEBIASAAN MEROKOK SERTA BAHAYANYA BAGI KESEHATAN MASYARAKAT DAN KESEHATAN LINGKUNGAN - Suratman, Suratman; Kuswanto, Kuswanto (Kesmas Indonesia: Jurnal Ilmiah Kesehatan Masyarakat, 2011)
A number of smokers in Indonesia place the third rank in the world. More than 60 million Indonesian people are a smoker. A death case due to a disease related to cigarette is about 427.948 persons every year or equal to 1.172 persons/day. The objective of this research was to describe a student?s understanding about smoking activity and negative effects for both public and environmental health. This study was observational research with cross-sectional approach. Population was all students at Public Health Department of Medicine and Health Sciences Faculty, Jenderal Soedirman University, Purwokerto with the following inclusion criteria: 1) Students who entered university from 2007 to 2009; 2) Male; 3) Students were still active attending lectures. Number of sample was seventy-six persons. The result of this research shows that most of the respondents have understood in terms of the negative effects of smoking for both public and environmental health even though some of them (28.95%) were a smoker. This research concludes that theoretically, they understand about the negative effects of smoking for health although some of them are a smoker. As a suggestion, students should make cooperation with Non-Government Organization (NGO) to advocate a local government in order to implement a regulation of a smoking ban. Kata Kunci : Smoking, Negative Effects for Health, Student  Kesmas indo. Volume 4(1,)Januari 2011, hlm. 11-23